Advanced PHP for Web Professionals - Cosentino, Christopher (Prentice Hall PTR advanced Web development series., 2002)
Build complex, PHP-driven Web sites-fast! Discover powerful new PHP techniques, hands on! Learn all-new techniques based on PHP-GTK and PEAR::DB Master XML parsing, user authentication, forms processing, data mining, and much more Take your PHP programming skills to the next level! In this concise, hands-on tutorial, PHP expert Christopher Cosentino delivers dozens of powerful new techniques for building serious Web applications. Through professional-quality examples drawn from his six years as a PHP developer, Cosentino walks you through building friendlier, more usable sites; improving user authentication; generating dynamic graphics; parsing XML documents; building database-independent Web applications; and much more! Take PHP to the limit... and beyond! Manage sessions more effectively Interact with multiple databases via PEAR::DB Improve your form processing scripts Parse large files and perform data mining Authenticate users by IP address, database query, or HTTP authentication Create custom error handlers Dump database contents into XML files Use PHP-GTK to build client-side cross-platform GUI applications And more...